Gynaecology : Evidence-based algorithms - Pundir, Jyotsna (Cambridge university press, 2016)
Content: early pregnancy care; disorders of menstruation; reproductive medicine; subfertility; urogynaecology, pelvic floor problems and hormone replacement therapy; gynaecological oncology;...